2006
DOI: 10.1021/bp050261i
|View full text |Cite
|
Sign up to set email alerts
|

Production of Islet-Like Structures from Neonatal Porcine Pancreatic Tissue in Suspension Bioreactors

Abstract: The aim of this study was to develop a scaleable process to expand pancreatic endocrine tissue (i.e., aggregates or islet-like structures) in suspension bioreactors. Key issues addressed included (i) serum-free media, (ii) cell inoculation density, (iii) medium pH, and (iv) aggregate dissociation. Suspension bioreactors were inoculated with pancreatic neonatal tissue and operated under controlled conditions for a 9-day period. Medium studies showed that a new serum-free medium developed in our laboratory was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
(39 reference statements)
0
15
0
1
Order By: Relevance
“…42 This has included production of insulin containing cells in stirred porcine pancreatic cell aggregate cultures. 43 However, attempts to differentiate or redifferentiate expanded pancreatic tissue into insulin-producing cells have involved typically cell aggregation 44,45 and/or immobilized culture in matrices. 46,47 Small (\1 mm) alginate beads are generated commonly by a vibrating nozzle, coaxial gas flow or cutting of a laminar jet by rotating blades (JetCutter).…”
Section: Potential Applicationsmentioning
confidence: 99%
“…42 This has included production of insulin containing cells in stirred porcine pancreatic cell aggregate cultures. 43 However, attempts to differentiate or redifferentiate expanded pancreatic tissue into insulin-producing cells have involved typically cell aggregation 44,45 and/or immobilized culture in matrices. 46,47 Small (\1 mm) alginate beads are generated commonly by a vibrating nozzle, coaxial gas flow or cutting of a laminar jet by rotating blades (JetCutter).…”
Section: Potential Applicationsmentioning
confidence: 99%
“…Mouse breast cancer stem cells expanded as aggregates in an instrumented and controlled stirred bioreactor retained the potential for clonal growth, including secondary colony formation [13••]. Culturing pig neonatal pancreatic tissue in spinner flasks led to the production of islet-like aggregates [14]. Although the number of cells decreased during the 9-day culture, the fraction of endocrine cells and the number of insulin-positive cells increased.…”
Section: Stem Cell Expansion and Differentiation In Bioreactorsmentioning
confidence: 99%
“…It is important to note that upon 18 h of culturing, the cells displayed high In fact, using porcine, rat and bovine dispersed islets, rat insulinoma-derived cell lines or human embryonic stem cells, maintained in immobilized suspension cultures, some reports show cell proliferation and insulin secretion, pointing to the effective expansion of islet-like tissue in bioreactors. 15,17,[19][20][21][22] A problem with this procedure is that the majority of the MCs were partially covered, suggesting that additional efforts towards improving the final cell yield have yet to be made. The observation that, with time, the cell clusters tend to dissociate from the MCs could, in part, explain the increased frequency of empty MCs at later time points in the bioreactor cultures.…”
Section: Research Papermentioning
confidence: 99%
“…13,14 It has recently been reported that porcine neonatal islets cultured in bioreactors were able to proliferate and exhibit a glucose responsive behavior. 15 In the present study, we set out to establish a method for immobilization of human pancreatic cells by attachment to Cytodex1 MCs (positively charged cross-linked dextran beads) (Pharmacia) and to standardize parameters for their culture in bioreactors by evaluating cell number and insulin secretion. This strategy offers an advantage over whole islet cultures since it minimizes the risk of anoxia for cells located at the core of each islet, representing a useful tool for controlled studies on islet cells physiology and, also, for biotechnological applications.…”
Section: Introductionmentioning
confidence: 99%